Journaling program development as an effort to improve student literacy skills - Harefaningtyas, Widya (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
The phenomenon of the low literacy level of elementary school students that occurs at UPTD SDN 3 Kerticala has an impact on students' common writing and reading skills. One alternative way that can be done to improve literacy skills in students, especially writing skills, is with a journaling training program. The type of research the author uses is qualitative research with descriptive methods. The subject of implementing this journaling program is class IV with 9 students. The procedure used in this study is the action class, which consists of 4 stages: (1) planning, (2) implementation of the action, (3) observance or observation, and (4) reflection. There were still deficiencies in the research conducted, as this research was not very in-depth and only carried out once. Hence, the results could have been more optimal, and there were no significant results from implementing programs designed to improve students' literacy skills at UPTD SDN 3 Kerticala. This limitation is expected to be a reference for improvement and further program development.